War Crimes: Evolution, Conceptualization, Categorization and Challenges - Açikalin, Oğuzhan Emre; Şeker Aydın, Gülşen (Current Perspectives in Social Sciences, 2025)
This study focuses on war crimes using a multi-disciplinary approach, which comprises history, law, and international relations. It employs case study methodology by using both primary and secondary resources. The main objective is to provide a clear, valid, and up-to-date framework to analyze war crimes and apply this framework to both historical cases and those occurring after the Cold War. To this end, having introduced the scope and importance of the subject, the study moves on to discussing theoretical and historical backgrounds. The third section analyses the narrow and broad conceptualizations of war crimes comparatively. It finds that it is necessary to adopt the narrow conceptualization to avoid ambiguity. As the categories included in the narrow conceptualization, this section also focuses on the war crimes against protected persons and objects and the war crimes related to unlawful means and methods of warfare. The following sections examine each category of war crimes in the light of historical and recent examples and find that war crimes were punished when powerful parties deemed necessary. The study concludes by emphasizing that political will is essential for punishing war crimes, and weak parties are still vulnerable to wartime violence to a large extent despite all the advances in the prosecution and punishment of war crimes in line with the premises of Realism on power and law versus those of Liberalism.